2000
DOI: 10.2527/2000.784846x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters among weight, prolificacy, and wool traits of Columbia, Polypay, Rambouillet, and Targhee sheep.

Abstract: Genetic parameters for Columbia, Polypay, Rambouillet, and Targhee sheep were estimated using REML with animal models for prolificacy, weight, and wool traits. All bivariate analyses included a covariance between additive genetic effects for the two traits plus appropriate additional covariances. Number of observations by breed ranged from 5,140 to 7,095 for prolificacy traits, from 7,750 to 9,530 for weight traits, and from 4,603 to 34,746 for wool traits. Heritability estimates ranged from .03 to .11 for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
52
11
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 27 publications
43
52
11
2
Order By: Relevance
“…This might have contributed to lower estimates. Estimates of c² pe for reproduction traits accord to estimates reported by Bromley et al (2000) (0.01 to 0.07)…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…This might have contributed to lower estimates. Estimates of c² pe for reproduction traits accord to estimates reported by Bromley et al (2000) (0.01 to 0.07)…”
Section: Resultssupporting
confidence: 76%
“…The estimates obtained for number of lambs born and weaned were generally low. The h² estimate for number of lambs born per ewe lambing (0.06) presented in Table 5 falls within the range of literature estimates (0.03 -0.12) (Brash et al, 1994b;Bromley et al, 2000;Rosati et al, 2002;Cloete et al, 2002a;b;. In the case of number of lambs weaned per ewe lambing, the estimate was 0.03.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The genetic correlation between prolificacy and birth weight was close to zero. Bromley et al (2000) concluded that birth weight and prolificacy were only slightly genetically correlated, with mostly different genes involved in the expression of these two traits. The genetic correlations between prolificacy and weaning weight, 12 month weight, 18 month weight, ewe mating, post-partum and ewe weight at weaning were 0.…”
Section: Resultsmentioning
confidence: 99%
“…Also, seasonal character of the oestrus incidence and lactation has to be eliminated and fertility has to exceed two lambs per sheep and partus. _____________________________________________________________________________________ In order to achieve these high objectives, permanent genetic improvement of traits which are of interest to breeders is necessary (Lewis et al, 1996, Okut et al, 1999, Sakul et al, 1999, Bromley et al, 2000, Petrović et al, 2003, 2004, 2005, 2006.…”
Section: Introductionmentioning
confidence: 99%